Modelling extended lactations of dairy cows - Vargas Leitón, Bernardo (1999)
General objective:Compare existing models on their ability to provide consistent predictors of partial and total milk yield in extended lactations. General conclusion:Diphasicmodel best fits extended lactationsand provides accurate estimates of total and partial milk yield.